Associations of Smoking With Delirium and Opioid Use in Older Adults With Traumatic Hip Fracture. (13th May 2022) - Salottolo, Kristin; Meinig, Richard; Fine, Landon; Kelly, Michael; Madayag, Robert; Ekengren, Francie; Tanner, Allen; Bar-Or, David
Abstract : Introduction: Cigarette smoking is a risk factor for hip fractures, while risk factors for developing delirium include older age and preexisting cognitive impairment. We sought to determine whether smoking status is independently associated with delirium and pain outcomes. Methods: This was a prospective, observational cohort study of 442 older adults (65 to 90 years) admitted for traumatic hip fracture at five trauma centers. The primary exposure was smoking status (n = 43, 10%). Additional risk factors included demographics, injury characteristics, and medical interventions. Delirium (primary) and analgesia-related complications were examined with multivariable logistic regression, while analysis of covariance models were used to examine preoperative and postoperative pain scores and opioid consumption (oral morphine equivalents). Results: Smokers had significantly worse outcomes compared with nonsmokers: delirium incidence was 16.3% versus 5.0% (adjusted odds ratio, 4.23; P = 0.005), analgesia complications developed in 30.2% versus 14.8% (adjusted odds ratio, 2.63; P = 0.01), and postoperative opioid consumption was greater (53 mg versus 33 mg, adjusted P = 0.04). Adjusted pain scores were not different between groups. Discussion: Smoking status is associated with markedly worse outcomes in older adults with traumatic hip fracture. Smoking status should be considered in pain management protocols and for early screening and delirium prevention methods. Data availability: On reasonable request.